2016
DOI: 10.1590/0103-8478cr20141666
|View full text |Cite
|
Sign up to set email alerts
|

Metabolizable energy levels for meat quails from 15 to 35 days of age

Abstract: This trial was carried out to evaluate the effects of dietetic metabolizable energy levels on performance and carcass traits of meat quails from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…When the levels of 2,700 and 3,100 kcal kg -1 were compared, there was a 1.9 g reduction in feed intake. These results are in agreement with those reported by Muniz et al (2016), who observed decreased feed intake with increasing level of apparent metabolizable energy (2,850-3,250 kcal kg -1 ) in diets for quails.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…When the levels of 2,700 and 3,100 kcal kg -1 were compared, there was a 1.9 g reduction in feed intake. These results are in agreement with those reported by Muniz et al (2016), who observed decreased feed intake with increasing level of apparent metabolizable energy (2,850-3,250 kcal kg -1 ) in diets for quails.…”
Section: Resultssupporting
confidence: 93%
“…The growing production demand in the area of coturniculture is accompanied by the need for knowledge of the nutritional management of quails. This practice has often been based on breeders experience, due to the scarce research conducted in Brazil on nutritional requirements for quails, especially for European quails (Muniz et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%
“…These results corroborate those found by Muniz et al 13 , evaluating ME levels different for growing quail, which also observed a significant effect on the reduction of feed intake with the increase of ME in the diet. This confirms the theory that birds regulate feed intake according to ME content in the diet.…”
Section: Discussionsupporting
confidence: 92%
“…The reduction in carcass weight as the feed energy level increased may be associated with a lower intake of feed and nutrients in the free-range broiler chicken. The lower intake of feed, which shows a loss in the utilization of these nutrients and in the rates of protein deposition, leads to suboptimal carcass composition (Muniz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%